(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
In this study, chromatographic conditions were developed for the separation and quantification of N-nitrosodimethylamine (NDMA) by HPLC. Our method would be useful for the rapid screening and quantification of NDMA impurity in Metformin hydrochloride, Losartan potassium, Valsartan and Ranitidine drugs substance and its products. The chromatographic separation was achieved on a Phenomenex C18 column (250 mm, 5 µm, 4.6 mm) by multistep gradient elution, using a water-acetonitrile mobile phase containing 0.1% formic acid, which provided better c hromatographic separation. Column temperature was maintained at 30℃; mobile phase flow rate: 1 mL/min; wavelength: 254 nm; and injection volume of 20 μL.